2009
DOI: 10.1007/s12393-009-9011-7
|View full text |Cite
|
Sign up to set email alerts
|

Review: Potential of High-Intensity Pulsed Electric Field Technology for Milk Processing

Abstract: Among nonthermal treatments, high-intensity pulsed electric field (HIPEF) has received special attention on account of its potential use in treating liquid foods and its feasible application in continuous-flow processing. Improving the food quality of milk and dairy products with HIPEF processing may be a relevant consideration in product development research. However, the future implementation of HIPEF equipment on an industrial scale may require more studies into the effects of the process parameters on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 64 publications
(120 reference statements)
0
17
0
1
Order By: Relevance
“…Temperature can also modify density, viscosity, as well as electrical and thermal conductivity of different foods; as a consequence, electric field distribution and product flow are intrinsically coupled to temperature variations [84]. Therefore, to maintain a non-thermal operation, the energy input to the food being treated must be controlled.…”
Section: Pef Treatment Chambersmentioning
confidence: 99%
See 2 more Smart Citations
“…Temperature can also modify density, viscosity, as well as electrical and thermal conductivity of different foods; as a consequence, electric field distribution and product flow are intrinsically coupled to temperature variations [84]. Therefore, to maintain a non-thermal operation, the energy input to the food being treated must be controlled.…”
Section: Pef Treatment Chambersmentioning
confidence: 99%
“…Moreover, these types of statistical design allow researchers to reduce the number of assays required for a full factorial design, thereby omitting information that may be unnecessary for statistical conclusions [84]. Food industry could apply this approach in order to optimize PEF process for food preservation.…”
Section: Implementing and Monitoring A Pef Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have demonstrated the effectiveness of PEF processing for microbial reduction in simulated milk ultra-filtrate and skim milk [28]. However, presence of fat and protein moieties limits the adeptness of PEF in whole milk because these molecules protect bacterial cells during treatment [29].…”
Section: Bacterial Inactivation In Milk By Pefmentioning
confidence: 99%
“…Although solid foods are susceptible to be processed by PEF (Puertolas et al 2010;De Vito et al 2008), this nonthermal technique as preservation method has mainly been assayed in liquid foods, such as juices (Hodgins et al 2002;Liang et al 2002;Mosqueda-Melgar et al 2008;Sampedro et al 2009;Zhang and Mittal 2005), fermented beverages (Iu et al 2001;Liang et al 2006;Ulmer et al 2002), liquid egg (CalderonMiranda et al 1999b;Pina-Pérez et al 2009), milk (Smith et al 2002;Sobrino-López et al 2006b;Sobrino-López and Martín-Belloso 2010;Walkling-Ribeiro et al 2009a) and dairy products (Gallo et al 2007). PEF also exhibits antimicrobial activity against: gram-positive bacteria, such as Spahylococcus aureus (Sobrino-López et al 2006b), Listeria innocua (Calderon-Miranda et al 1999a), Micrococcus luteus (Dutreux et al 2000) and Bacillus cereus (Pina-Pérez et al 2009); gram-negative bacteria, such as Escherichia coli (Iu et al 2001) and Salmonella typhimurium (Liang et al 2002); spores when they are submitted to a pre-germination treatment, such as Bacillus subtilis (Shin et al 2010); yeasts (McNamee et al 2010;Zhang and Mittal 2005); and moulds (Evrendilek et al 2008).…”
Section: Introductionmentioning
confidence: 99%